SOCIAL MATURITY OF PERSONALITY AS FACTOR OF BECOMING OF PROFESSIONAL MATURITY OF PSYCHOLOGIST - Komar, T. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article is an attempt for theoretical and empirical analysis of the problem of the relationship of social maturity and direction of professional maturity of personality psychologist. The topic investigated the features of interrelation of individual social maturity and direction of professional maturity psychologist in the process of formation.Overview research positions on the structure of social maturity, we identified the following components:cognitive-motivational component presupposes knowledge of social ideas and values of the individual; social intelligence, divergent thinking, creativity, planning their own life scenario, life crises knowledge, understanding social reality, the choice of profession;reflective component – provides mental self-control feelings psychosexual literacy, independence, understanding of social roles, the ability to feel the nuances of social situations, solve problem situations responsibility;operational and technological components – characterized by a certain social experience, skills of effective interaction with society, the ability to operate adequately, a variety of techniques behavior, performance of social roles, the ability to leave the conflict.The level of development and the formation of social intelligence and its structural components; dominant communication styles and leading communication skills; the priority of personal orientation are determined. Discovered level of social intelligence and competent communication style together constitute an adequate level of social competence is correlated with the dominant orientation of the individual – focus on interaction and communication, and business orientation. It should be noted that the detected result corresponds to features and specifics of the training of future psychologists, humanistic orientation of their professional activities.
Keywords: social maturity, professional development, professional maturity of expert, level of social intelligence, social determinants of maturity